Storm Clouds Ahead? : Migration and Labor Force Participation Rates in Europe - Hilgenstock, Benjamin; Koczan, Zsoka (Washington, D.C. : International Monetary Fund, 2018)
The paper examines the potential effects of international migration on labor force participation in advanced economies in Europe. It documents that migration played a significant role in alleviating aging pressures on labor supply by affecting the age composition of receiving countries' populations. However, micro-level analysis also points to differences in average educational levels, as well as differences in the effects of any given level of education on participation across migrants and natives. Difficulties related to the recognition of educational qualifications appear to be associated with smaller effects of education on the odds of participation for migrants, especially women.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet